Chaplin's Essanay comedies part 2 - Chaplin, Charlie 1889-1977 (Essanay Film Mfg., Co., 1915)
Charlie the tramp meets a girl, falls in love, and saves her and her home from three hobos, only to find out that she is already engaged. In By the sea, Charlie gets into a long fight with a man over their hats and ice cream. Charlie works as a paper-hanger and gets involved in his employer's problem with his wife and her lover. Two men fall for Charlie when he dresses up as a woman. Charlie works as a janitor in The bank and dreams of saving the manager and Edna in a bank robbery.